2018
DOI: 10.1097/icu.0000000000000484
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of herpetic keratitis

Abstract: Several options are available for surgically managing the complications of herpes keratitis. Ophthalmologists should select the optimal procedure based on the individual patient's situation. VIDEO ABSTRACT: http://links.lww.com/COOP/A28.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Currently, the main treatments of HSK are topical and oral agent antiviral drugs that inhibit the replication of the virus in the cornea . However, in order to preserve the eyeball and recover corneal clarity, surgical intervention may be required for patients with corneal dissolution or long‐term complications such as ulcers, necrotizing keratitis, and neurotrophic keratitis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the main treatments of HSK are topical and oral agent antiviral drugs that inhibit the replication of the virus in the cornea . However, in order to preserve the eyeball and recover corneal clarity, surgical intervention may be required for patients with corneal dissolution or long‐term complications such as ulcers, necrotizing keratitis, and neurotrophic keratitis …”
Section: Introductionmentioning
confidence: 99%
“…5 However, in order to preserve the eyeball and recover corneal clarity, surgical intervention may be required for patients with corneal dissolution or long-term complications such as ulcers, necrotizing keratitis, and neurotrophic keratitis. 6 Currently, the lack of donor corneas is a major problem for corneal transplantation especially in Asian countries. 7 Many patients miss the best time for treatment whilst waiting for donor cornea tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that therapeutic grafts for herpetic keratitis have poor outcomes. In addition to a signi cant rate of rejection and recurrence, hypoesthesia secondary to the loss of nerve cells may provoke exposure keratopathy [24]. Our study included two patients with herpetic keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Trifluridine (TFT) eye drop, acyclovir (ACV) ointment, ganciclovir (GCV) gel, and oral ACV are still the main therapeutic agents for treatment of ocular HSV infection (Roozbahani and Hammersmith, 2018;Valerio and Lin, 2019). Surgical treatment may be necessary to treat complications arising from HSV keratitis (Tuli et al, 2018). The animal models of HSV vaccine are able to reduce HSV keratitis (Dong et al, 2017;Tang et al, 2018;Royer et al, 2019).…”
Section: Discussionmentioning
confidence: 99%